2017
DOI: 10.2147/jbm.s129516
|View full text |Cite
|
Sign up to set email alerts
|

The risk of renal disease is increased in lambda myeloma with bone marrow amyloid deposits

Abstract: Background Light chain amyloidosis (AL) is a rare deposition disease and is present in 10–15% of patients with myeloma (MM). In contrast to symptomatic AL in MM, presence of bone marrow (BM) amyloid deposits (AD) in MM is not connected to kidney damage. Renal AD but not BM-AD occur mostly in MM with lambda paraprotein (lambda MM). Methods We investigated amyloid presence in BM clots taken at diagnosis in 84 patients with symptomatic MM and compared disease characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
(48 reference statements)
1
2
0
1
Order By: Relevance
“…These data shows that occurrence of AL and its severity significantly affect the survival of patients with MM, even in the current new drug era. 2,12,[16][17][18][19][20][21][22][23][24][25][26] Although a high level of baseline 24-hour proteinuria has been proposed as a marker of renal involvement and progression of renal dysfunction, our current research data showed that kidney involvement does not have a major impact on survival, similar to existing research results. 2,21 Forty-eight percent of patients who showed abnormal genes of TP53 deletion, and t(14;16) and 1q21 amplification had shorter OS than other patients (8 vs. 26.5 months), favoring the adverse effects of these high-risk genes on survival.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These data shows that occurrence of AL and its severity significantly affect the survival of patients with MM, even in the current new drug era. 2,12,[16][17][18][19][20][21][22][23][24][25][26] Although a high level of baseline 24-hour proteinuria has been proposed as a marker of renal involvement and progression of renal dysfunction, our current research data showed that kidney involvement does not have a major impact on survival, similar to existing research results. 2,21 Forty-eight percent of patients who showed abnormal genes of TP53 deletion, and t(14;16) and 1q21 amplification had shorter OS than other patients (8 vs. 26.5 months), favoring the adverse effects of these high-risk genes on survival.…”
Section: Discussionsupporting
confidence: 88%
“…3,5 Among them, 62% of patients contained lambda light chain in their M protein, and the kidneys and heart were the 2 most commonly affected organs, which is similar to the literature. 3,[16][17][18][19] More than 10% of clonal plasma cells and high levels of M protein, especially immunoglobulin light chain levels, can be present in both MM and AL, and CRAB symptoms caused by malignant plasma cell disease are unique to MM. Therefore, while MM and AL the two diseases were combined exist, refer to the method of Mayo Clinic, CRAB symptoms were the key points for diagnosing MM.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with light chain lambda show a significantly shorter survival (median OS 10 vs. 30 months for lambda and kappa respectively) as described by Shustik et al [39]. Expression of the lambda chain was associated with a predisposition to extramedullary localization and rapidly progressive renal failure [40,41].…”
Section: Discussionmentioning
confidence: 65%
“…In AL amyloidosis, a plasma cell clone produces a misfolded, monoclonal light immunoglobulin chain that often has the propensity to be deposited in the glomerulus, a feature that is more common with lambda chains due to their potential to dimerize [21]. Overall, light chain deposits constitute around 80% of all renal cases of amyloid deposition.…”
Section: Q7: How Does Al Amyloidosis Affect the Kidneys?mentioning
confidence: 99%